Therapeutic approach in Class I malocclusion with impacted maxillary canines - Matheus Melo PITHON (Dental Press Editora, 2022)
ABSTRACT Objective: To emphasize the importance of diagnosis and discuss the therapeutic approaches that can be used in the orthodontic treatment of Class I malocclusion associated with two impacted maxillary canines. The opening of spaces for traction of these teeth by means of rapid maxillary expansion or extraction of maxillary premolars was contraindicated in the case reported. Therefore, it was decided to open spaces with projection of incisors. Results: The obtained results were satisfactory, as a good occlusion was obtained, with adequate functional guides, as well as an improvement in the facial appearance. Conclusion: The projection of the incisors prior to traction of the impacted maxillary canines proved to be a valid option in the case described. Ten years after completion of treatment, the case is stable, maintaining periodontal health.